2017
DOI: 10.1103/physrevlett.118.145902
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Hall Effect in a Phonon-Glass Ba3CuSb2O9

Abstract: A distinct thermal Hall signal is observed in a quantum spin liquid candidate Ba3CuSb2O9. The transverse thermal conductivity shows a power-law temperature dependence below 50 K, where a spin gap opens. We suggest that because of the very low longitudinal thermal conductivity and the thermal Hall signals, a phonon Hall effect is induced by strong phonon scattering of orphan Cu 2+ spins formed in the random domains of the Cu 2+ -Sb 5+ dumbbells in Ba3CuSb2O9.Hall measurements of metals are fundamental tools to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 44 publications
(127 reference statements)
4
50
1
Order By: Relevance
“…However, a closely related honeycomb-lattice antiferromagnetic material Bi 3 Mn 4 O 12 (NO 3 ) [12] shows evidence of magnetic order at a critical field of ∼ 6 Tesla consistent with a collinear Néel order [13]. Prior to this experimental report, we have already shown that honeycomb (anti)ferromagnet with a next-nearest-neighbour staggered DMI captures a negative κ xy and power-law temperature dependence κ xy ∝ T 2 [14,15] as recently seen in Ba 3 CuSb 2 O 9 [2]. In this regard, we believe that this correspondence between theory and experiment cannot be serendipitous.…”
supporting
confidence: 70%
See 3 more Smart Citations
“…However, a closely related honeycomb-lattice antiferromagnetic material Bi 3 Mn 4 O 12 (NO 3 ) [12] shows evidence of magnetic order at a critical field of ∼ 6 Tesla consistent with a collinear Néel order [13]. Prior to this experimental report, we have already shown that honeycomb (anti)ferromagnet with a next-nearest-neighbour staggered DMI captures a negative κ xy and power-law temperature dependence κ xy ∝ T 2 [14,15] as recently seen in Ba 3 CuSb 2 O 9 [2]. In this regard, we believe that this correspondence between theory and experiment cannot be serendipitous.…”
supporting
confidence: 70%
“…This effect has been previously observed in collinear ferromagnetic materials with DMI [3][4][5] and pyrochlore spin liquid material [6]. In these recent reports, a transverse thermal Hall conductivity κ xy was observed in a strong magnetic field ∼ 15 Tesla applied perpendicular to the plane of the frustrated magnets [1,2]. The observed effect on the Kagomé volborthite is attributed to spin excitations in the spin liquid (SL) regime.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…More stoichiometric samples manage to preserve their room-temperature hexagonal symmetry down to much lower temperatures either through a dynamic JT effect [34] or else local distortions that nonetheless preserve the global symmetry of the structure and give rise to a random-singlet magnetic ground state [7]. The most recent experimental results, thermal conductivity measurements, on nearly stoichiometric single-crystal Ba 3 CuSb 2 O 9 point toward the local-distortion picture [35] which is consistent with the random singlet magnetic ground state and excitation gap [7]. Since a hexagonal to orthorhombic collective JT transition can be ruled out by the neutron diffraction results on the materials studied here, similar random distortions might then apply, and they may be ex- The high frequency data has been normalized so that the peak susceptibilities are equal, since the frequency response of the PPMS system is not perfectly flat.…”
Section: Collective Magnetic Ground Statesmentioning
confidence: 99%